Expression Profile of Pyroptosis-Related Genes and the Associated Regulatory Axis in Primary Gout Patients - Niu S; Lei TY; Dai F; Xie H; Yu X; Zhang Q; Qing Y (Dove Medical Press, 2023)
Shaowei Niu,1- 3,* Tian-Yi Lei,2,3,* Fei Dai,2,3,* Hongyuan Xie,2,3 Xiang Yu,2,3 Quanbo Zhang,1,2,4 Yufeng Qing1- 3 1The First Affiliated Hospital, Jinan University, Guangzhou, People's Republic of China; 2Research Center of Hyperuricemia and Gout, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of China; 3Department of Rheumatology and Immunology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of China; 4Department of Geriatrics, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of China*These authors contributed equally to this workCorrespondence: Yufeng Qing; Quanbo Zhang, Research Center of Hyperuricemia and Gout, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan Province, People's Republic of China, Tel/Fax +86 08172282131, Email qingyufengqq@163.com; quanbozhang@126.comPurpose: Analyzed the expression characteristics of pyroptosis-related genes (PRGs) in peripheral blood mononuclear cells (PBMCs) of gout patients by microarray, and constructed ceRNA network to explore the molecular mechanism of RNA-mediated pyroptosis regulation.Patients and Methods: Human mRNA, lncRNA, circRNA microarray data were used to identify differentially expressed in PBMCs from patients with primary gout and healthy controls. Differential PRGs in PBMCs of gout patients identified by Genecard database and mRNA microarray data. GO and KEGG enrichment analyses of these genes were then conducted. Protein-protein interaction networks and cytoHubba were used to identify hub genes. Combining the lncRNA and circRNA microarray data, a ceRNA network was constructed by Cytoscape to screen out key non-coding RNA molecules that can regulate target PRGs. Finally, the relative expression levels of target miRNA and circRNA in 60 gout patients and 40 healthy subjects were detected by qRT-PCR.Results: The results revealed 30 differentially expressed PRGs. GO and KEGG analysis of these genes were mainly concentrated in the production and regulation of cytokines, NOD-like receptor signaling pathway and so on. Nine hub genes were screened by PPI network, including IL1B, DDX3X, NLRP3, NLRP9, AIM2, CASP8, P2XR7, CARD8 and IFI16. The has_circRNA_102906\hsa_circRNA_102910\hsa_circRNA_102911-hsa-miR-129-5p-DDX3X\NLRP3\NLRP9 regulatory network was constructed. The expression of has_circRNA_102906, hsa_circRNA_102910, hsa_circRNA_102911 were up-regulated and hsa-miR-129-5p down-regulated in PBMCs of gout patients. The relative expression of hsa_circRNA_102911 was positively correlated with clinical inflammatory indicators associated with gout, and the area under the curve of hsa_circRNA_102911 for gout diagnosis was 0.85 (95% CI: 0.775- 0.925; p < 0.001).Conclusion: There are several differentially expressed PRGs in PBMCs of gout patients, which are involved in the regulation of gout inflammation through multiple pathways. hsa_circRNA_102911-hsa-miR-129-5p-DDX3X\NLRP3\NLRP9 may be the key regulatory pathway for pyroptosis to regulate gout inflammation, and hsa_circRNA_102911 may be a potential biomarker for the diagnosis of primary gout.Keywords: gout, pyroptosis, endogenous competitive RNA, peripheral blood mononuclear cells, bioinformatics